Multi-Criteria Vertical Handover by TOPSIS and Fuzzy Logic - Alkhawlani, Mohammed M.; Alsalem, Kasim A.; Hussein, Aref A. (IEEE, 2011)
In the next generation heterogeneous wireless networks, a user with a multi-interface terminal may have network access from different service providers using various technologies. Vertical Handover (VHO) is the capability to switch on-going connections from one Radio Access Network (RAN) to another. This switching is based on the discovered accesses, QoS constraints, operator policies, user preferences and available system capacity and utilization. Optimizing the VHO process is an important issue of research, which leads to reduction of network signalling and mobile device power loss and on the other hand improves network quality of service (QoS) and grade of service (GoS). In this paper, a decision support system is developed to address the VHO problem. This system combines fuzzy logic and TOPSIS, a MCDM algorithm, to the problem of VHO. This combination decreases the influence of the dissimilar, imprecise, and contradictory measurements for the VHO criteria coming from different sources. A performance analysis is done and results are compared with traditional algorithms for VHO. These results demonstrate a significant improvement with our developed algorithm.